Integrating Complex Soil Dynamics Using the Non-equilibrium Effective Temperature - Almquist, Vance W. (Frontiers in Earth Science, 2020)
Soil dynamics, such as aggregate turnover, play central roles in modulating global cycles of carbon, nitrogen and water. However, understanding soil dynamics, and the role they play in soil system functioning is complicated by the fact that soils naturally exhibit scale-dependent physical and chemical variability across more than a dozen orders of magnitude in both space and time. Herein it is argued that scale-dependent soil variability emerges at large scales in part because soils systems, in the larger sense, are non-equilibrium thermodynamic systems. One driver of soil disequilibrium is pedoturbation, or soil stirring. Soil stirring is widely implicated in affecting long-term processes such as aggregation, horizonation, and rates of chemical weathering. This observation aligns well with advancements recently made in theoretical physics. For a variety of non-equilibrium physical systems , the stirring rate has been shown to be equivalent to an effective temperature of the system, and can be used to recover thermodynamic relationships in non-equilibrium settings. This work primarily presents the mathematical basis for calculating the effective temperature, a measurement approach, and discusses the implications of this framework on several outstanding problems within soil science. While effective temperatures have yet to be measured in soils, this framework has the potential to greatly simplify and compliment the modeling of complex soil dynamics, but also potentially provide a new tool to rectify the discordance between small and large scale rates of soil processes.